Africa: Taking fire safety forwards. (3rd August 2020) - Walls, Richard S.; Cicione, Antonio; Messerschmidt, Birgitte; Almand, Kathleen
Summary: The population of Africa has increased rapidly, with a population of 630 million in 1990 exploding to a population of 1.2 billion in 2016. Furthermore, across the continent, there is rapid urbanisation combined with a significant growth in mining, mineral processing, transportation, fuel storage, energy generation and industrial activities. This has resulted in the fire risk for the continent growing exponentially in the past decades, and it is the cause for serious concern that there are very few educational, research and regulatory bodies providing the necessary training and knowledge basis to keep the continent safe from fire. It is with this background that this paper seeks to provide: (a) a high‐level overview of Africa's recent growth and development, that is illustrated with (b) a number of recent disasters that present events that could become more commonplace if action is not taken which (c) is used to explain the growing fire risk on the continent, and leads to the proposal of (d) a high‐level roadmap for producing a continent that is more resilient to fire. International data from developed countries are used to demonstrate how the application of fire engineering standards and knowledge has improved fire safety and reduced losses in various developed countries, and Africa could potentially follow this trend, although there are significant challenges that must be faced.